DISTRIBUTION AND BIO-PHYSICAL CHARACTERISTICS OF RESERVOIRS IN INDO-GANGETIC BASIN (IGB) IN RELATION TO THEIR FISHERIES - SARKAR, SANCHITA; KATIHA, PRADEEP K.; PAL, M. K. (Journal of the Inland Fisheries Society of India, 2021)
The reservoirs located in Indian IGB were assessed to establish relation between their bio-physical and institutional characteristics with fisheries management and fish yield. The analyses of information gathered from 521 IGB reservoirs revealed that i) >80% reservoirs had area